Development of pachycoris torridus (hemiptera: scutelleridae) on jatropha curcas (euphorbiaceae), psidium cattleianum (myrtaceae) and aleurites fordii (euphorbiaceae) - Borges Filho, Raul Da Cunha; Pratissoli, Dirceu; Nava, Dori Edson; Monte, Fernanda Garcia; Guidoni, Antonio Lourenco; Dos Anjos E Silva, Sergio Delmar; Polanczyk, Ricardo Antonio [UNESP] (Florida Entomological Soc, 2013)
Pachycoris torridus (Scopoli, 1772) (Hemiptera: Scutelleridae) is a polyphagus insect and is traditionally considered the key-pest of jatropha (Jatroph acurcas L.; Malpighiales: Euphorbiaceae); however, occurrences of this pest have also been observed on strawberry guava (Psidium cattleianum Sabine; Myrtales: Myrtaceae) and the tung tree (Aleurites fordii Hemsl.; Malpighiales: Euphorbiaceae). This study investigated the development of P. torridus in fruits of jatropha, strawberry guava and tang to provide information for phytosanitary management of this pest. We evaluated the biological parameters in the nymphal and adult stages of the pest at 25 2 C, RH 70 10% and 12:12 h (L:D). Nymphs of P. torridus did not develop in fruits of tung. In fruits ofjatropha and strawberry guava, P. torridus had 5 instars of nymphal development with variable durations and survival rates. The nymphal stage showed durations and viabilities of 55 days and 33.7% and 56.1 days and 38.9% in strawberry guava and jatropha, respectively. The sex ratio (proportion of females in the population) was 0.6 in strawberry guava and 0.5 in jatropha. The weights of adult females and males were greater in jatropha (152.0 and 117.2 mg) than in strawberry guava (127.9 and 105.9 mg). Females fed with jatropha showed a longer pre-oviposition period and shorter periods of oviposition and post-oviposition than those fed on strawberry guava. Fecundity was similar in both treatments (hosts). Fruits of strawberry guava and jatropha are adequate for the development and reproduction of P. torridus.
Keywords: Hemiptera; stinkbug of jatropha; hosts; Biology